Health communication in low-income countries: A 60-year bibliometric and thematic analysis - Nour Mheidly; Jawad Fares (Wolters Kluwer Medknow Publications, 2020)
BACKGROUND: Health communication is a field that uses social and behavioral models to improve health outcomes and raise awareness on major health risks that threaten human well-being. Low-income countries (LICs) suffer from the effects of communicable and noncommunicable diseases that are exacerbated by weak health-care systems, lack of awareness campaigns, and ineffective communication tactics. This work aims to explore health communication research in LICs to find strategies that help improve health outcomes in the future. MATERIALS AND METHODS: The PubMed database was explored systematically for publications related to health communication from LICs between January 1, 1960, and January 1, 2020. Publications were categorized according to country of origin and were analyzed with respect to population size, gross domestic product (GDP), and primary school enrollment of each state as obtained from the World Bank Open Data. RESULTS: Collectively, LICs published 796 contributions, comprising 1.08% of the total biomedical research published by LICs and 0.27% of the world's health communication research. Malawi had the highest number of publications per GDP, with 32.811 publications per billion US$. Uganda had the most contributions per population, with 9.579 publications per million persons. Ethiopia had the highest amount of contributions per primary school enrollment with a ratio of 2.461 publications per %gross. The role of health communication in promoting HIV awareness and prevention was the most common theme explored. Other infectious diseases, such as malaria, tuberculosis, and Ebola, were also highlighted. Improving communication in health education was also explored. CONCLUSION: Health communication is a rising field in LICs, with research focusing on disease prevention. Efforts to amplify research are key to effectively utilize the health communication models and improve health outcomes in LICs.